Pengaruh Stres terhadap Gangguan Menstruasi Selama Pembelajaran Online di Masa Pandemi Covid-19 - Salsabila Aulia Putri; Herri S. Sastramihardja; Mira Dyani Dewi (Bandung Conference Series: Medical Science, 2023)
Abstract. The Coronavirus Disease 2019 (COVID-19) pandemic prompted the government to implement social distancing. One of them is online distance learning. The impact of online learning can cause stress and anxiety, especially for medical students. Stress stimulates the hypothalamus pituitary adrenal cortex axis (HPA Axis) to produce the hormone cortisol and causes irregular menstrual cycles due to hormonal imbalances including reproductive hormones. The purpose of this study was to determine the relationship between stress and menstrual disorders in female students at the Faculty of Medicine, Bandung Islamic University class of 2019 during online learning during the COVID-19 pandemic. This research was reviewed by the Bandung Islamic University Ethics Committee with letter number 126/KEPK-Unisba/IV/2022. This research method was conducted with an observational analytic design and used a cross-sectional study. The research material used was the Perceived Stress Scale-10 (PSS-10) questionnaire and the menstrual cycle questionnaire for 50 female students who were included in the inclusion criteria. Based on the results of the study, it was shown that as many as 42 people (84%) experienced abnormal menstrual cycles and only 8 people (16%) were normal and the majority of the results of this study were female students who experienced moderate levels of stress, namely 28 respondents (56%). There is a significant relationship between stress and the menstrual disorders. These results are proven by using a statistical test with Chi-Square and with a p-value = 0.005 (<0.05). Abstrak. Pandemi Coronavirus Disease 2019 (COVID-19) mendorong pemerintah untuk menerapkan social distancing. Salah satunya adalah pembelajaran jarak jauh secara online. Dampak pembelajaran online dapat menimbulkan stres dan kecemasan, khususnya Mahasiswa Kedokteran. Stres merangsang hypothalamus pituitary adrenal cortex axis (HPA Axis) untuk memproduksi hormon kortisol dan menyebabkan menstruasi tidak teratur karena ketidakseimbangan hormonal termasuk hormon reproduksi. Tujuan penelitian ini adalah untuk mengetahui Hubungan Stres dan Gangguan Menstruasi pada Mahasiswi Fakultas Kedokteran Universitas Islam Bandung Angkatan 2019 Selama Pembelajaran Online di Masa Pandemi COVID-19. Metode penelitian ini dilakukan dengan desain analitik. Bahan penelitian yang digunakan menggunakan kuesioner Perceived Stress Scale-10 (PSS-10) dan kuesioner gangguan menstruasi kepada 50 mahasiswi yang termasuk kriteria inklusi. Berdasarkan hasil penelitian menunjukkan bahwa sebanyak 42 orang (84%) mengalami menstruasi tidak normal dan hanya 8 orang (16%) normal dan mayoritas dari hasil penelitian ini adalah mahasiswi yang mengalami tingkat stres pada kategori sedang yaitu sebanyak 28 responden (56%). Terdapat hubungan bermakna antara Stres dengan Gangguan Pada Mahasiswi di Fakultas Kedokteran Universitas Islam Bandung Selama Pembelajaran Online di Masa Pandemi COVID-19. Hasil ini dibuktikan dengan menggunakan uji statistik dengan Chi-Square dan dengan p-value = 0,005 (< 0,05).